Poverty in Selected European Countries. A Spatio-temporal Analysis from 2003–2020 - Jewczak, Maciej; Korczak, Karol (Comparative Economic Research. Central and Eastern Europe, 2023)
The problem of poverty, both in theory and practice, gained a new meaning with the beginning of the transformation of selected European economies from being centrally planned to market economies. The transition and the accompanying ownership changes resulted in significant shifts in the income distribution, which affected the increase in the stratification of society in terms of material situation and the deterioration of the living conditions of some social groups. Developing and evaluating anti‑poverty programs should be preceded by identifying who is considered poor. Defining poverty is the first and a key step in measuring its characteristics, e.g., its intensity. Hence, the choice of a specific definition of poverty is of fundamental importance for the results of this measurement. The aim of the paper is to assess the material situation of European societies in terms of poverty change in a holistic approach – considering all the information available in international statistics on the problem. To achieve the research objective at the regional data level, we used the URi measure to decompose changes in structure and estimate the direction and intensity of poverty recorded. Further, we evaluated whether the transformations coincide temporarily and spatially. Applying the Hellinger distance (HD) allowed us to identify the significance of trends in changes in the poverty structure, especially in the years of the COVID–19 pandemic, when an increase in the importance of individual structural components of poverty was observed in the analysed European NUTS–2 spatial units. For some economies, the transition was also a consequence of European economic crises or major events of international importance, e.g., sports events or countries acceding to the EU.